KONFLIK ANTAR KELUARGA PADA ORANG TOLAKI DI DESA LALONGGOWUNA KECAMATAN TONGAUNA KABUPATEN KONAWE - Aswatin Aswatin; Syamsumarlin Syamsumarlin; Hasniah Hasniah (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2017)
In Kolese Village, District of Pasikolaga, Muna Regency, there is a traditional treatment of Bhisa kantisele. It cures diseases that cannot be cured by medical treatment. This study aims to determine the causes and characteristics of diseases as well as to know the treatment process of tisele by Bhisa kantisele in Kolese Village, Pasikolaga District, Muna Regency. Data collection is done by direct observation techniques and in-depth interviews. The data were analyzed descriptively qualitatively. Data analysis is intended to simplify the data so that it is more readable and understood. The results of this study show that, there are several characteristics of tisele that can be treated by kantisele bhisa which include pale, lack of appetite, insomnia, sudden shock, not sneezing the body feels cold during the day and feels constant fear and trembling body. There are several treatment processes for tisele which are carried out by Bhisa Kantisele, which detects patient's disease, reads prayers (bhatata) on certain body parts, namely the soles of the feet, knees, center, neck, right ear, left ear, and crown, and recite prayers (bhatata) in a glass of water. The equipment uses corn cob media, water and prayers (bhatata). Bhisa kantisele in the community in Kolese Village is very trusted and has been proven to cure tisele. The villagers consider the tisele disease that they suffer can only be cured by bhisa kantisele and cannot be cured by medical treatment.